1972
DOI: 10.1007/bf01867862
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin and α-amanitin: Inhibitors of transcription as probes of aldosterone action

Abstract: Summary. Evidence has been presented for the existence of distinct ]~NA polymerases (I and II) in the rat kidney similar to those described previously in rat liver and identified as nucleolar (I) and nucleoplasmic (II) in location. In adrenalectomized rats, administration of d-aldosterone (1 ~tg/100 g body wt) increased the ratio of polymerase I:II activity as defined by sensitivity to a-amanitin. The time-course of this shift correlated with the previously reported changes in urinary Na and K concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 34 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…The effectiveness of the inhibitors actinomycin D (14) and a-amanitin (15) also supports a specific role of mRNA in the induction of calcium-binding protein and calcium transport. Yet, numerous other hormones such as testosterone (32) and aldosterone (33) [6][7][8][9] hr is consistent with the lag time for metabolism of the native vitamin to la,25-(OH)r2 D3 and supports our present finding of a direct effect of the hormonal sterol in 2-3 hr (Fig. 2).…”
Section: Discussionsupporting
confidence: 88%
“…The effectiveness of the inhibitors actinomycin D (14) and a-amanitin (15) also supports a specific role of mRNA in the induction of calcium-binding protein and calcium transport. Yet, numerous other hormones such as testosterone (32) and aldosterone (33) [6][7][8][9] hr is consistent with the lag time for metabolism of the native vitamin to la,25-(OH)r2 D3 and supports our present finding of a direct effect of the hormonal sterol in 2-3 hr (Fig. 2).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Spooner and Edelman (1975) found that aldosterone stimulation of both I~-and transepithelial electrical conductance depended on the metabolic state. (iv) The differential response to substrate repletion 3 to 4 hr after the addition of aldosterone is insensitive to inhibitors of RNA and protein synthesis added at the time of substrate repletion (Fanestil, Herman, Fimognari & Edelman, 1968;Chu & Edelman, 1972). Taken together these results imply that the increase in PN~ is not a sole consequence of synthesis of new channel proteins.…”
Section: Metabolic Dependence Of Channel Recruitmentmentioning
confidence: 82%
“…The mean values were taken from the data in Figs. [2][3][4][5] in which a 30-min [3H]uridine pulse and 90-to 150-min chase were used. These populations cover a wide range of responses from no increase in SCC after SC 9420 or cortisol to maximum increases elicited by aldosterone.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of findings support this hypothesis including: the presence of nuclear receptors in target tissues (2), effects of inhibitors of RNA and protein synthesis (3)(4)(5)(6), and effects on specific mitochondrial enzymes (7), RNA polymerase activity (5,8), chromatin template activity (9), and incorporation of precursors into total or nuclear RNA (10)(11)(12)(13). Precise definition of regulation of transcription by aldosterone, however, has not yet been achieved.…”
mentioning
confidence: 99%